Field-based evidence for consistent responses of bacterial communities to copper contamination in two contrasting agricultural soils - Li, Jing; Ma, Yi-Bing; Hu, Hang-Wei; Wang, Jun-Tao; Liu, Yu-Rong; He, Ji-Zheng (Frontiers in Microbiology, 2015)
Copper contamination on China’s arable land could pose severe economic, ecological and healthy consequences in the coming decades. As the drivers in maintaining ecosystem functioning, the responses of soil microorganisms to long-term copper contamination in different soil ecosystems are still debated. This study investigated the impacts of copper gradients on soil bacterial communities in two agricultural fields with contrasting soil properties. Our results revealed consistent reduction in soil microbial biomass carbon (SMBC) with increasing copper levels in both soils, coupled by significant declines in bacterial abundance in most cases. Despite of contrasting bacterial community structures between the two soils, the bacterial diversity in the copper-contaminated soils showed considerably decreasing patterns when copper levels elevated. High-throughput sequencing revealed copper selection for major bacterial guilds, in particular, Actinobacteria showed tolerance, while Acidobacteria and Chloroflexi were highly sensitive to copper. The thresholds that bacterial communities changed sharply were 800 and 200 added copper mg kg-1 in the fluvo-aquic soil and red soil, respectively, which were similar to the toxicity thresholds (EC50 values) characterized by SMBC. Structural equation model (SEM) analysis ascertained that the shifts of bacterial community composition and diversity were closely related with the changes of SMBC in both soils. Our results provide field-based evidence that copper contamination exhibits consistently negative impacts on soil bacterial communities, and the shifts of bacterial communities could have largely determined the variations of the microbial biomass.